2014
DOI: 10.1186/1471-2458-14-799
|View full text |Cite
|
Sign up to set email alerts
|

Active commuting to school, cognitive performance, and academic achievement: an observational study in Dutch adolescents using accelerometers

Abstract: BackgroundThe current study examined the associations between active commuting to school, cognitive performance, and academic achievement in Dutch adolescents. In addition, it was explored whether these associations were moderated by sex and mediated by depressive symptoms.MethodsStudents in grades 7 and 9 (N = 270; mean age 13.4 years; 53% boys) were included. Active commuting to school was measured objectively by an ActivPAL3™ accelerometer. Cognitive performance was measured by the d2 Test of attention (key… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
76
0
8

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(90 citation statements)
references
References 44 publications
6
76
0
8
Order By: Relevance
“…The finding of this study that ACS was not related with academic performance is an accordance with one study (Van Dijk et al, 2014) but not with another one (Martínez-Gómez et al, 2011), that found a positive association only in girls. A potential explanation of the lack of findings of analysed outcomes is that adolescents reported their 'usual' methods of commuting to and from school.…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…The finding of this study that ACS was not related with academic performance is an accordance with one study (Van Dijk et al, 2014) but not with another one (Martínez-Gómez et al, 2011), that found a positive association only in girls. A potential explanation of the lack of findings of analysed outcomes is that adolescents reported their 'usual' methods of commuting to and from school.…”
Section: Discussionsupporting
confidence: 80%
“…This compared to about 50% in US studies (McDonald et al, 2011). Other European studies have found that about 50% and 65% of youth lived within, respectively, 1 mile (Van Sluijs et al, 2009) and 1.4 miles (Panter et al, 2011), suggesting that more US youth live farther from their schools. Since distance is the most consistent barrier of ACS (Davison et al, 2008;Lu et al, 2014;Pont et al, 2009), this might help to explain the higher prevalence of youth ACS found in this and other European studies (Pooley et al, 2005;Van Sluijs et al, 2009) when compared to US studies, where fewer than 15% of youth are walking and cycling to school (McDonald et al, 2011).…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations